Business models for nature-based tourism companies: The adoption of sustainable requirements - Abreu, C.; Marques, C.; Pereira, H. G. (Journal of Rural Studies, 2026)
Nature-based tourism is increasingly recognised as a strategic segment within the tourism sector, often dominated by small and family-owned enterprises. Despite its growing relevance, the adoption of explicit, sustainable business models in this segment remains limited, with many firms operating in informal or implicit approaches. Although business models are acknowledged as key mediators of innovation and sustainability, substantial gaps remain in understanding and applying innovative sustainable business model principles within nature-based tourism companies. This study provides novel empirical evidence by examining how these companies integrate sustainability into their business models and by examining the requirements and practices adopted by nature-based tourism entrepreneurs. This study provides novel empirical evidence by examining how these companies engage with the four guiding principles proposed by Breuer et al. (2018) (sustainability orientation, extended value creation, systems thinking and stakeholder integration) and the constraints they face in doing so. Building on these principles, the research explores how sustainability is integrated into existing business models. An exploratory qualitative study based on thirteen semi-structured interviews with Portuguese nature-based tourism entrepreneurs reveals that, although sustainability is widely regarded as essential for competitiveness and long-term resilience, its integration into business models remains uneven and largely intuitive. Environmental aspects receive more systematic attention than social value creation, systems integration or stakeholder collaboration, with progress hindered by limited managerial capabilities, resource scarcity, and weak policy alignment. The study contributes to the literature by clarifying how sustainability principles are operationalised in small tourism enterprises and by identifying structural barriers that prevent their fuller adoption. It also offers practical implications for policymakers and support institutions seeking to strengthen the resilience, competitiveness and sustainability orientation of nature-based tourism systems.